PENGARUH AKTIVITAS PENGENDALIAN, INFORMASI DAN KOMUNIKASI TERHADAP KUALITAS SISTEM INFORMASI AKUNTANSI DAN DAMPAKNYA TERHADAP KUALITAS LAPORAN KEUANGAN (Studi Kasus Pada Badan Pemeriksa Keuangan Republik Indonesia) - Syafrida Dwi Rachmawati; Fardinal Fardinal (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2017)
This research was motivated because no integrated with software in the examination of the financial statements of the central government because recording of cash receipts and the Directorate General of Taxes point a different amount. By looking at existing problems, the study aims to know the influence of control activities, information and communication to quality of accounting information system and the quality of financial report. The study collected data from 50 respondents. Questionnaires were distributed to Unit BPK RI and 40 questionnaires were returned. The answer of Respondents were then Analyzed with a statistical assessment of SEM-PLS. The result of the research shows that control activities influences significant to quality of accounting information system, information and communication influences is not significant to quality of accounting information system, and quality of accounting information system influences significant to quality of financial report.